2015
DOI: 10.3748/wjg.v21.i14.4373
|View full text |Cite
|
Sign up to set email alerts
|

Ipilimumab associated colitis: An IpiColitis case series at MedStar Georgetown University Hospital

Abstract: Although ipilimumab has been shown to improve survival in patients with metastatic melanoma and cause regression of metastatic renal cell carcinoma, the associated immune-related toxicities are of concern. The resultant T cell activation by this monoclonal antibody causes an increased immune response, which has been associated with many immune-regulated adverse effects. One of the most concerning effects is the development of colitis. Upwards to 8% of patients have been reported to develop colitis, with 5% bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…The pathogenesis of colitis and other iAEs from ipilimumab remains unclear. Prior studies have described similar histopathological features in Ipi‐AC as inflammatory bowel disease (IBD) , although no study to our knowledge has directly compared these two disease entities. Although Ipi‐AC has been hypothesized to result from depletion of T regulatory (Treg) cells and activation of T effector cells in the gastrointestinal (GI) tract , studies describing the immunophenotypic features of the GI mucosa in Ipi‐AC are limited and conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of colitis and other iAEs from ipilimumab remains unclear. Prior studies have described similar histopathological features in Ipi‐AC as inflammatory bowel disease (IBD) , although no study to our knowledge has directly compared these two disease entities. Although Ipi‐AC has been hypothesized to result from depletion of T regulatory (Treg) cells and activation of T effector cells in the gastrointestinal (GI) tract , studies describing the immunophenotypic features of the GI mucosa in Ipi‐AC are limited and conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 1892 unique studies identified using our search criteria, 61 studies fulfilled our inclusion criteria and were included in the qualitative analysis (38 full text articles, 23 in abstract form) . Results of our search strategy are depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Funnel plots were produced for the principal outcome for each comparison, and Egger's test of funnel plot asymmetry was used to assess publication bias. 27 All statistical analyses described above were performed using the STATA (version 16) software. Reporting of this study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement.…”
Section: Data Synthesis and Statistical Methodsmentioning
confidence: 99%